Polyconvolution formation of finite integral transformations - Kakichev, V. A. (Mathematical Modelling and Analysis, 1997)
“Polyconvolution formation of finite integral transformations”Mathematical Modelling Analysis, 2(1), p. 79-83.First Published Online: 14 Oct 2010